no 4.
using substitution method
2x - y = 5...(i)
3x + 2y = 4...(ii)
making y subject of formula in (i)
2x-y=5
2x-5=y
substitute y in (ii)
3x+2(2x-5)=4
opening bracket
3x+4x-10=4
collecting like terms
3x+4x=4+10
7x=14
dividing both sides by 7
7x/7=14/7
x=2.
but y=2x-5
y=2(2)-5
y=-1.
solution=(2,-1)
no.12.
3x+2y=7...(i)
5x-4y=19...(ii)
multiply (i) by 2 and (ii) by 1
3x+2y=7}×2
5x-4y=19}×1
we get;
6x+4y=14
5x-4y=19
adding the two equations,
6x+5x=11x
4y+-4y=0
14+19=33
new equation
11x=33
divide both sides by 11
11x/11=33/11
x=3
replacing x in (i)
3x+2y=14
3(3)+2y=14
9+2y=14
2y=14-9
dividing both sides by 2
2y/2=5/2
y=5/2 or 2.5
solution=(3,5/2) which is not in the choices.